Signet-ring carcinoma arising on duodenal brunner's gland adenoma - L. Masu; M. Pinamonti; S. Coverlizza (Elsevier, 2020)
We present a rare case of a 66-year-old male with radiological evidence of a polypoid mass in the first section of the duodenum. He first received on biopsy the diagnosis of Brunner's gland adenoma with foci of signet-ring invasive carcinoma, "diffuse-type", and after two months he underwent distal gastrectomy extended to the first section of duodenum. The resected specimen contained, on the intestinal surface, one solid, stalked polyp of 2,5 cm (maximum diameter). Morphological assessment and immunohistochemistry were performed and the previous diagnosis of an infiltrating signet-ring cells adenocarcinoma arising on Brunner's gland was confirmed.Brunner's gland adenomas are rare tumors of the duodenum. These lesions have previously been described as benign. Some authors described epithelial dysplasia associated with surface erosions, suggesting a malignant potential. In the literature, just few cases of adenocarcinoma originating from Brunner's glands adenoma are described. As far as we know, there have been no previous reports about pure signet-ring adenocarcinomas arising from Brunner's glands polyp.First diagnosis on biopsy is difficult and could be even more insidious within surgical specimen. This is due to extensive erosions, massive loss of surface epithelium, inflammation, fibrosis and hyperplastic changes, especially when facing with an adenocarcinoma infiltrating in a single-cell manner. Based on our experience, for patient's better surgical and oncologic management, we think it is important to look carefully at the polyp surface while at the same time considering all the potential pitfalls.